ANALISIS METODE NETNOGRAFI PADA AKTIVITAS AKUN YANG BERPERAN SEBAGAI AKTOR YANG MEMICU PERANG DI MEDIA SOSIAL - Ita Nulita; Henri Subiakto; Titik Pudji Rahayu (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
The information generated by the hate spread of accounts on social media after the 2019 presidential election is increasingly widespread even though the political contestation has ended. The emergence of warring political accounts on social media continues to this day. This study aims to analyze accounts that act as actors who spread hate speech issues on social media, especially on Facebook and Instagram. The method used is netnography. The results of the study show that, first, there is a network of actors who control accounts on social media. Second, the discovery of groups of accounts that act as actors, namely the Counter-Government Actor Group and the Pro Actor Group. Therefore, it can be concluded that this war on social media uses an offensive pattern that is used as a way of self-defense.